Airframe manufacturers: Which has the better view of the future? - Mason, Keith J. (Elsevier Science B.V., Amsterdam., 2007)
For the development of Airbus' A380 and Boeing's B787 it seems that these manufacturers have differing views of future airline networks. This paper assesses from published sources the likely preferences of leisure and business passengers for different airline network approaches and also assesses airline strategies through the economic cycle. The manufacturers seem to have substitutable aircraft types. Both leisure and business travellers are increasingly price elastic and growth in both markets means both aircraft type will be successful aircraft meeting differing needs. However, airline market- share strategies are likely to undermine the success of hub by-pass or hub-to- hub focus strategies throughout the cycle. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: airframe manufacturers Boeing Airbus hub and spoke hub by-pass